2000
DOI: 10.1136/heart.83.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary arteriovenous shunting may be a universal phenomenon in patients with the superior cavopulmonary anastomosis: a radionuclide study

Abstract: Objective-To evaluate the extent of intrapulmonary right to left shunting in children after bidirectional cavopulmonary anastomosis (BCPA). Design-Prospective study of patients who underwent BCPA in a single centre. Patients-17 patients with complex cyanotic congenital cardiac malformations who underwent BCPA at 1-45 months of age (median 21 months) were evaluated 15-64 months postoperatively (median 32 months). Five children between 1 and 10 years (median 5 years) with normal or surgically corrected intracard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 30 publications
4
53
0
1
Order By: Relevance
“…Pediatric congenital heart surgical experiences favor similar hypotheses. [12][13][14] What circulating mediators should or could be measured? We await such innovation, discoveries, and genetic profiles.…”
Section: Commentsmentioning
confidence: 99%
“…Pediatric congenital heart surgical experiences favor similar hypotheses. [12][13][14] What circulating mediators should or could be measured? We await such innovation, discoveries, and genetic profiles.…”
Section: Commentsmentioning
confidence: 99%
“…The incidence is reported to be between 16.9% [7] and 25% [8]. In contrast to these macroscopic fistulas diffuse right-to-left-shunts can be seen shortly after BDG with symptomatic cyanosis [9].…”
Section: Discussionmentioning
confidence: 90%
“…Subsequent reports indicate that the prevalence of PAVS in these patients may be higher [1,10]. Using radionuclide-labeled microspheres, Vettukattil et al found that all patients developed some degree of PAVS following CPA [21]. It has been suggested that children undergoing Glenn CPA at a younger age are more likely to develop fulminant PAVS [1].…”
Section: Discussionmentioning
confidence: 99%